Comfort vs risk: a grounded theory about female adolescent behaviour in the sun. Issue 13 (25th December 2013) - Norton, Elizabeth; Holloway, Immy; Galvin, Kathleen
<x xml:space="preserve">Abstract</x> Aims and objectives To generate a grounded theory about female adolescent behaviour in the sun. Background Nurses have key roles in health promotion and skin cancer prevention. Adolescents' resistance to sun safety messages and their vulnerability to sunburn are of concern internationally. Understanding why young women do as they do in the sun may enhance skin cancer prevention, but their behaviour has not been explained before in the UK. Design The study incorporated a qualitative grounded theory design using the approach of Glaser. Methods Qualitative data were gleaned from group and one‐to‐one, semi‐structured interviews with 20 female participants aged 14–17, research memos and literature. Sampling was purposive and theoretical. Data collection, analysis and theory generation occurred concurrently. Data were analysed using the constant comparative method. Data collection ended when a substantive theory had been generated. Results Data analysis revealed five categories of findings: fitting in, being myself, being physically comfortable, slipping up and being comfortable (the core category). The theory generated around the core explains how young women direct their sun‐related activities towards meeting their physical and psychosocial comfort needs. Conclusions A contribution of this research is the grounded theory explaining the behaviour of young women in the sun. Further, the theory challenges assumptions that female adolescents necessarily take risks; it explains their sun‐related activities in terms of comfort. The theory extends findings from other researchers' descriptive qualitative studies and also appears to apply to young people in countries other than the UK. Relevance to clinical practice Understanding the sun‐related activity of young women in terms of physical and psychosocial comfort may help nurses to develop new approaches to skin cancer prevention. These could complement existing messages and humanise health promotion.